2019
DOI: 10.1111/psyp.13352
|View full text |Cite
|
Sign up to set email alerts
|

A common neural substrate for elevated PTSD symptoms and reduced pulse rate variability in combat‐exposed veterans

Abstract: Previous studies have identified reduced heart rate variability (HRV) in post‐traumatic stress disorder (PTSD), which may temporally precede the onset of the disorder. A separate line of functional neuroimaging research in PTSD has consistently demonstrated hypoactivation of the ventromedial prefrontal cortex (vmPFC), a key aspect of a descending neuromodulatory system that exerts inhibitory control over heart rate. No research to date, however, has simultaneously investigated whether altered vmPFC activation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Replicating prior studies, treatment with paroxetine resulted in an increase in anterior cingulate/medial prefrontal (BA 24, 32) function in women with PTSD. Multiple studies have shown a decrease in anterior cingulate/medial prefrontal function ( Bluhm et al, 2012 ; Bremner et al, 1999a , 1999b , 2004 ; Britton et al, 2005 ; Clausen et al, 2017b ; Dahlgren et al, 2018 ; Elzinga and Bremner, 2002 ; Fonzo et al, 2010a ; Frewen et al, 2012 ; Gold et al, 2011 ; Grupe et al, 2020 ; Hopper et al, 2007 ; Hou et al, 2007 ; King et al, 2009 ; Lanius et al, 2001 , 2004 , 2003 ; Liberzon et al, 2003 , 1999 ; Lindauer et al, 2004 ; New et al, 2009 ; Offringa et al, 2013 ; Phan et al, 2006 ; Pissiota et al, 2002 ; Shin et al, 1997 , 1999 , 2004 ; Shin et al, 2001 , 2005 ; St Jacques et al, 2011 , 2013 ; Yang et al, 2004 ) and connectivity ( Akiki et al, 2018 ; Amad et al, 2019 ; Birn et al, 2014 ; Clausen et al, 2017b ; Disner et al, 2018 ; Gong et al, 2014 ; Jin et al, 2014 ; Kennis et al, 2015 ; Liu et al, 2016 ; Misaki et al, 2018 ; Sadeh et al, 2015 ) in PTSD. Treatment with paroxetine ( Fani et al, 2011 ; Zhu et al, 2015 ) transcutaneous vagal nerve stimulation ( Wittbrodt et al, 2021 ) or hydrocortisone ( Metz et al, 2019 ) in PTSD patients resulted in an increase in function in this region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Replicating prior studies, treatment with paroxetine resulted in an increase in anterior cingulate/medial prefrontal (BA 24, 32) function in women with PTSD. Multiple studies have shown a decrease in anterior cingulate/medial prefrontal function ( Bluhm et al, 2012 ; Bremner et al, 1999a , 1999b , 2004 ; Britton et al, 2005 ; Clausen et al, 2017b ; Dahlgren et al, 2018 ; Elzinga and Bremner, 2002 ; Fonzo et al, 2010a ; Frewen et al, 2012 ; Gold et al, 2011 ; Grupe et al, 2020 ; Hopper et al, 2007 ; Hou et al, 2007 ; King et al, 2009 ; Lanius et al, 2001 , 2004 , 2003 ; Liberzon et al, 2003 , 1999 ; Lindauer et al, 2004 ; New et al, 2009 ; Offringa et al, 2013 ; Phan et al, 2006 ; Pissiota et al, 2002 ; Shin et al, 1997 , 1999 , 2004 ; Shin et al, 2001 , 2005 ; St Jacques et al, 2011 , 2013 ; Yang et al, 2004 ) and connectivity ( Akiki et al, 2018 ; Amad et al, 2019 ; Birn et al, 2014 ; Clausen et al, 2017b ; Disner et al, 2018 ; Gong et al, 2014 ; Jin et al, 2014 ; Kennis et al, 2015 ; Liu et al, 2016 ; Misaki et al, 2018 ; Sadeh et al, 2015 ) in PTSD. Treatment with paroxetine ( Fani et al, 2011 ; Zhu et al, 2015 ) transcutaneous vagal nerve stimulation ( Wittbrodt et al, 2021 ) or hydrocortisone ( Metz et al, 2019 ) in PTSD patients resulted in an increase in function in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Brain imaging studies have outlined a network of brain areas mediating memory and the fear response in PTSD ( Akiki et al, 2017 ; Boccia et al, 2016 ; Campanella and Bremner, 2016 ; Dixon et al, 2017 ; Etkin and Wager, 2007 ; Fitzgerald et al, 2018 ; Francati et al, 2007 ; Koch et al, 2016 ; Patel et al, 2012 ; Sartory et al, 2013 ; Thome et al, 2020 ; Wang et al, 2016 ). Brain imaging studies involving activation of PTSD symptoms using behavioral paradigms like trauma-related pictures, sounds and/or personalized scripts resulted in decreased function or failure of activation in the medial prefrontal cortex (mPFC)/anterior cingulate cortex (ACC) ( Bremner et al, 1999a , 1999b ; Dahlgren et al, 2018 ; Lanius et al, 2001 , 2003 ; Lindauer et al, 2004 ; Offringa et al, 2013 ; Phan et al, 2006 ; Shin et al, 1997 , 1999 , 2004 ; Shin et al, 2001 , 2005 ), ventromedial prefrontal cortex ( Bluhm et al, 2012 ; Grupe et al, 2020 ; Milad et al, 2009 ; Phan et al, 2006 ; Rougemont-Bücking et al, 2011 ; Sanjuan et al, 2018 ), thalamus ( Elman et al, 2018 ; Lanius et al, 2001 , 2003 ; Schechter et al, 2012 ), fusiform gyrus ( Cwik et al, 2017 ; Osuch et al, 2001 ), precuneus ( Geuze et al, 2008a ; Lanius et al, 2002 ; Werner et al, 2009 ), cuneus ( Cortese et al, 2018 ; Cwik et al, 2017 ; Lindauer et al, 2004 ; Misaki et al, 2019 ; Morey et al, 2009 ; Ramage et al, 2013 ; Sun et al, 2019 ), visual association cortex ( Bremner et al, 1999a ; Gold et al, 2011 ; Lanius et al, 2001 , 2003 ; Shin et al, 1997 , 2004 ...…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings have also been reported at rest ( Thome et al, 2017 ). Furthermore, Grupe et al (2020) investigated neural responses of the anticipation of predictable and unpredictable conditioned threat and safety cues in individuals with high and low PTSD symptoms related to combat. A relationship between HRV and higher-order cognitive control systems was observed during unpredictable threat vs. safety trials.…”
Section: Introductionmentioning
confidence: 99%
“…A lower vagal HRV component was associated with pre and post-combat development of post-traumatic stress disorder (PTSD) symptoms. Many studies have shown that patients with PTSD have lower HRV indices than healthy adults [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%